2013
DOI: 10.1097/scs.0b013e318264653f
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sinus Membrane Perforation on the Survival of Implants Placed in Combination With Osteotome Sinus Floor Elevation

Abstract: This study was conducted to evaluate implant survival with regard to effects of sinus membrane perforation that occurred during osteotome sinus floor elevation (OSFE). The study group consisted of 42 patients with edentulous posterior maxilla. Implants placement combined with OSFE without a grafting material was performed. All patients underwent a radiographic examination before surgery, to reveal the periimplant bone formation immediately after implant placement and 6 to 33 months later. Sinus membrane perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Thirteen studies reported the number of SM perforations and implants failure rate at the study level. Meta regression analyses from the random‐effects model (I 2 = 84%) showed that there was statistical significant and positive association ( P = .06) between implants failure rate and the number of SM perforation after SFE (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Thirteen studies reported the number of SM perforations and implants failure rate at the study level. Meta regression analyses from the random‐effects model (I 2 = 84%) showed that there was statistical significant and positive association ( P = .06) between implants failure rate and the number of SM perforation after SFE (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…At this stage of the analysis, 42 studies were excluded because they did not meet inclusion criteria. Finally, a total of 58 studies met the inclusion criteria and were processed for critical review …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations